Penerapan Metode Pembelajaran Matematika Berbasis ICT pada SDN 14 Kecamatan Lubuk Begalung Padang - Ranti Eka Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Learning media is a container, facilities or facilities that can provide convenience to educators to convey messages or information to be received well and interesting by students. Selection of appropriate learning media will give effect and influence in realizing the achievement of learning objectives. With the availability of instructional media, educators can create classroom situations, determine what teaching methods will be used in different situations and create a healthy emotional climate among learners. In the process of teaching and learning at SDN 14 Padang, what happens in learning often happen the teaching process runs ineffectively. A lot of time, and energy wasted while the goal of learning cant be achieved even happen noises or voice that is not important in communication between teachers and students. For that purpose, it is designed the instructional media which is devoted to the field of mathematics study in discussing material about multiplication, division, addition and subtraction by using Adobe Flash CS3. Keywords : Learning Media, ICT, Adobe Flash CS3